Guarding the heart in the era of immunotherapies: insights for cardio-oncology practice - Iram, Umamah; Lebeche, Djamel (Frontiers in Pharmacology, 2026)
The advent of cancer immunotherapies, including immune checkpoint inhibitors (ICI), Chimeric antigen receptor (CAR-T) cell therapies, and bispecific antibodies and other immune-activating platforms such as therapeutic vaccines and oncolytic viruses (often used in combination regimens) has revolutionized oncology by improving patient outcomes across diverse malignancies. However, these therapies are increasingly linked to cardiovascular toxicities such as myocarditis, arrhythmias, and heart failure, posing significant clinical challenges. Here we review current evidence on the mechanisms, clinical manifestations, diagnostic approaches, and management strategies of immunotherapy-associated cardiotoxicities, emphasizing the role of cardio-oncology in integrating cardiovascular care with cancer treatment. We also discuss emerging immunotherapies and their potential cardiac effects. Understanding these complexities is critical to optimizing patient safety and treatment efficacy. Continued interdisciplinary research and standardized clinical protocols are essential to advance early detection, risk stratification, and tailored interventions, thereby preserving the therapeutic benefits of immunotherapy while mitigating cardiovascular risks.